2015
DOI: 10.1016/j.ejvs.2015.03.058
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Clinical Success and Long-Term Durability of Endovascular Treatment for Atherosclerotic Aortic Arch Branch Origin Obstruction: Evaluation of 144 Procedures

Abstract: Endovascular treatment of aortic arch branch origin obstruction is safe and efficacious in experienced hands and can be considered as the preferred treatment, with good mid-term durability. Recurrent symptomatic lesions can be treated safely by renewed endovascular means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 14 publications
1
44
0
1
Order By: Relevance
“…The results of the largest series suggested stenting as the treatment of choice in selected patients (4). In addition, Chatterjee et al (5) showed that stenting is significantly superior to angioplasty alone.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the largest series suggested stenting as the treatment of choice in selected patients (4). In addition, Chatterjee et al (5) showed that stenting is significantly superior to angioplasty alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one patient suffered from a posterior fossa TIA owing to SAS recurrence. 6 In a more recent study, van de Weijer et al 26 analyzed data from 114 patients who underwent PTA of the subclavian, innominate, or the left common carotid artery over a mean follow-up of 52.0 months (range, 2-163 months); 27 patients (23.7%) became symptomatic again (15 brachiocephalic artery, 1 left common carotid artery, and 11 left subclavian artery). In 19 patients (70%), RS of the target lesion was found.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, most recanalizations are achieved with hydrophilic guidewires, which are primarily successful in subtotal occlusions. 2,3 However, there is well known significant difficulty and failures when encountering chronic total occlusions, mostly because of calcified caps at the ends of the CTO. 4 Other techniques employed for CTO crossing include controlled blunt micro-dissection, and optical coherence reflectometry guided RFA guidewires, again, however, not designed for this application.…”
Section: Discussionmentioning
confidence: 99%